2014
DOI: 10.2172/1184668
|View full text |Cite
|
Sign up to set email alerts
|

Design Report for the ½ Scale Air-Cooled RCCS Tests in the Natural convection Shutdown heat removal Test Facility (NSTF)

Abstract: Facility (NSTF)one of the world's largest facilities for ex-vessel passive decay heat removal testing-confirms the performance of reactor cavity cooling systems (RCCS) and similar passive confinement or containment decay heat removal systems in modern Small Modular Reactors. Originally built to aid in the development of General Electric's Power Reactor Innovative Small Module (PRISM) Reactor Vessel Auxiliary Cooling System (RVACS), the NSTF has a long history of providing confirmatory data for the airside of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The mesh convergence sensitivity study showed that the simulation results are highly dependent on the mesh refinement at the fluid-solid boundary, calling for very fine meshes near the reactor vessel surface due to the large temperature gradients at the wall. To examine the feasibility of an air-cooled RCCS option for advanced gas-cooled reactors, an experimental program was established at Argonne National Laboratory [58] in the early 2000s which revitalized the Natural convection Shutdown heat removal Test Facility (NSTF) built previously for RVACS testing in the 1980s. Compared to the legacy NSTF, the modern NSTF stood 26-m in total height and was designed to represent a 1:2 scale model of the primary features of the General Atomic (GA) RCCS design for the MHTGR [59].…”
Section: Air-cooled Rccsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mesh convergence sensitivity study showed that the simulation results are highly dependent on the mesh refinement at the fluid-solid boundary, calling for very fine meshes near the reactor vessel surface due to the large temperature gradients at the wall. To examine the feasibility of an air-cooled RCCS option for advanced gas-cooled reactors, an experimental program was established at Argonne National Laboratory [58] in the early 2000s which revitalized the Natural convection Shutdown heat removal Test Facility (NSTF) built previously for RVACS testing in the 1980s. Compared to the legacy NSTF, the modern NSTF stood 26-m in total height and was designed to represent a 1:2 scale model of the primary features of the General Atomic (GA) RCCS design for the MHTGR [59].…”
Section: Air-cooled Rccsmentioning
confidence: 99%
“…To examine the feasibility of an air-cooled RCCS option for advanced gas-cooled reactors, an experimental program was established at Argonne National Laboratory [58] in the early 2000s which revitalized the Natural convection Shutdown heat removal Test Facility (NSTF) built previously for RVACS testing in the 1980s. Compared to the legacy NSTF, the modern NSTF stood 26-m in total height and was designed to represent a 1:2 scale model of the primary features of the General Atomic (GA) RCCS design for the MHTGR [59]. The test section contained twelve riser ducts and served as the primary flow area for cooling within the heated cavity, Figure 48.…”
Section: Air-cooled Rccsmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements of system mass flow rates, differential pressure drop, surface and gas temperatures, among others, are included in this suite. A summary is provided in Table 1, with additional details such as the heater configuration and insulation properties provided in earlier works by the authors [6,7]. While it is expected that thermal radiation will be the primary mode of heat transfer, the heated cavity (essentially an internal enclosed environment) allows natural circulation cells to develop and grow.…”
Section: Full Scale Design Conceptmentioning
confidence: 99%